DIALECTIC FORMS OF LINGUISTIC IN THE NARRATIVE STRATEGY OF SHORT STORIES OF V. STEFANYK AND E. CALDWELL - Гнатюк, О. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights and compares the features of dialectal forms of language in the short stories of V. Stefanyk and E. Caldwell, as the dialect is one of the artistic means that reflects the individual peculiarities of artistic thinking of both masters.